Studi Optimasi Produktivitas Alat Gali Muat dan Alat Angkut Menggunakan Metode Linear Programming Pada Perolehan Produksi Overburden PT. Surya Global Makmur Jobsite Pemusiran, Kabupaten Sarolangun, Provinsi Jambi - Adinda Adinda; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. The coal mining business is currently faced with various challenges such as export spendingpolicies, increasing product value added, and decreasing product market prices. In order to be able tocompete, mining companies are required to increase productivity and increase and enhance sustainableproduction processes. In the mining process, the draw of dump truck equipment and loading equipmentwill determine the continuity of production which increases productivity and efficiency. The purpose of thisstudy is to optimize production in coal mining in order to efficiently use equipment by using linearprogramming methods. The location of the study was conducted in the PT Surya Global Makmur JobsitePemusiran mining concession area, Sarolangun Regency, Jambi Province in October 2019. The loadingequipment used was five units of backhoe excavators and 22 units of dump trucks. The results of thesimulation with linear programming methods are 20 units of conveyance. The results of productionoptimization with the linear programming method produce overburden productivity of 681.16 BCM perhour with an optimal cost of 0.86 USD / BCM.Keywords: Coal Mining, Overburden, Linear Programming, Production Optimize, and Optimal Cost